Brown spiders’ phospholipases-d with potential therapeutic applications: Functional assessment of mutant isoforms - da Silva, Thaís Pereira; de Castro, Fernando Jacomini; Vuitika, Larissa; Polli, Nayanne Louise Costacurta; Antunes, Bruno César; Bóia-Ferreira, Marianna; Minozzo, João Carlos; Mariutti, Ricardo Barros [UNESP]; Matsubara, Fernando Hitomi; Arni, Raghuvir Krishnaswamy [UNESP]; Wille, Ana Carolina Martins; Senff-Ribeiro, Andrea; et al. (MDPI, 2021)
Phospholipases-D (PLDs) found in Loxosceles spiders’ venoms are responsible for the der-monecrosis triggered by envenomation. PLDs can also induce other local and systemic effects, such as massive inflammatory response, edema, and hemolysis. Recombinant PLDs reproduce all of the deleterious effects induced by Loxosceles whole venoms. Herein, wild type and mutant PLDs of two species involved in accidents—L. gaucho and L. laeta—were recombinantly expressed and character-ized. The mutations are related to amino acid residues relevant for catalysis (H12-H47), magnesium ion coordination (E32-D34) and binding to phospholipid substrates (Y228 and Y228-Y229-W230). Circular dichroism and structural data demonstrated that the mutant isoforms did not undergo significant structural changes. Immunoassays showed that mutant PLDs exhibit conserved epitopes and kept their antigenic properties despite the mutations. Both in vitro (sphingomyelinase activity and hemolysis) and in vivo (capillary permeability, dermonecrotic activity, and histopathological analysis) assays showed that the PLDs with mutations H12-H47, E32-D34, and Y228-Y229-W230 displayed only residual activities. Results indicate that these mutant toxins are suitable for use as antigens to obtain neutralizing antisera with enhanced properties since they will be based on the most deleterious toxins in the venom and without causing severe harmful effects to the animals in which these sera are produced.
Keywords: Loxosceles; Mutant phospholipases-D; Phospholipases-D; Site-directed mutations; Venom enzymes